Critical analysis of early recurrence after laparoscopic radical cystectomy in a large cohort by the ESUT - Albisinni, Simone; Rassweiler, Jens (The journal of urology, 2016)
Purpose: We analyze patients with early progression after laparoscopic radical cystectomy in a large cohort by the ESUT (European Association of Urology Section of Uro-Technology). More specifically we focus on patients with favorable pathology (pT2 N0 R0 or less) who experienced an unexpected recurrence and analyze possible causes for such early recurrence, discussing the surgical technique including pneumoperitoneum. Materials and Methods: Since 2000 the ESUT has been constructing a large, multicenter, prospective database of patients undergoing laparoscopic radical cystectomy. All procedures were performed via a standard laparoscopic approach without robotic assistance. We specifically analyzed patients with favorable pathological characteristics, in particular pT2 N0 R0 or less, and evaluated those with progression despite these favorable characteristics. Univariate and multivariate logistic regression was performed to evaluate risk factors for early recurrence. Results: A total of 627 patients were available for final analysis with a median followup of 46 months (mean 57). Of these patients 311 had favorable pathological characteristics of pT2 N0 R0 or less. During followup 27 (8.7%) patients experienced disease progression during the first 24 months. Surgical negligence was found in only 1 case. Most of these patients with early recurrence had progression to high tumor volume disseminated metastatic disease. On multivariate logistic regression tumor stage was the only factor significantly associated with early recurrence (p=0.027). Conclusions: We report early unexpected recurrences after laparoscopic radical cystectomy in nearly 5% of our entire cohort, all in patients with favorable pathological characteristics (pT2 N0 R0 or less). Pneumoperitoneum may have had a role in the development of these relapses. Specifically designed studies are necessary to investigate the possible role of pneumoperitoneum in urothelial cancer recurrence.
Gesehen am 12.12.2019